Contribution to the knowledge of Coccinellidae (Coleoptera) of Iran. (3rd April 2019) - Biranvand, Amir; Hesami, Shahram; Gheibi, Mehdi; Fekrat, Lida; Nedvěd, Oldřich; Shakarami, Jahanshir
Abstract: Based on reviewing the previous relevant literature on Iranian ladybirds as well as identifying and studying coccinellid specimens collected during 2013–2016 from various localities in Lorestan province (Western Iran), a revised checklist of the Coccinellidae of Lorestan is presented, with 57 species from 25 genera of 10 tribes. Tytthaspis sedecimpunctata (Linnaeus, 1758) is excluded from the fauna of Lorestan, Clitostethus arcuatus (Rossi, 1794) and Nephus bipunctatus (Kugelann, 1794) are added to the fauna of Lorestan. Moreover, an identification key to the reported genera of Coccinellidae in Lorestan province, a key to the subgenera of Nephus Mulsant and Scymnus Kugelann and also a key to the species of subgenus Bipunctatus Fürsch in Iran are given.